Taxation and Consumers’ Spending Patterns in Nigeria: An Autoregressive Distributed Lag and Error Correction Model Approach - James, David; Omodero, Cordelia Onyinyechi; Nwobodo, Helen; Odhigu, Festus Onosakponome; Adeyemo, Kingsley Aderemi (International Journal of Economics and Financial Issues, 2024)
This study evaluates the effects of personal income tax and consumption tax on the spending system of consumers in Nigeria. The autoregressive distributed lag (ARDL) model has been employed for the co-integration test. The research additionally employs the Error Correction Model (ECM) to assess the pace at which any divergence from the long run equilibrium can return to normal in the current period. The findings show that Value added tax has an insignificant impact on purchasing power of consumers in both the short and long intervals. However, personal income tax and exchange rate exert substantial positive effect on consumer spending power in the long run but not in the short run. At the 1% level, the ECT coefficient is shown to be significant and unfavourable. This demonstrates a pretty slow convergence rate, with the model pushing itself towards equilibrium by 37% each year. The consequence is that any disequilibrium caused by shocks from the previous year requires 37% adjustment speed to return to long-run equilibrium in the current year. There have been several studies on how consumption tax affects households’ welfare without considering the effects of income tax and ever fluctuating exchange rate alongside these whole scenarios. This study puts all of these issues into consideration and contributes meaningfully to the existing literature that personal income tax is an integral part of the factors that affect households’ spending capacity. The study recommends that proper tax policy to enhance consumers’ spending capacity.